Anglo-French Relations and Strategy on the Western Front, 1914–18 - Philpott, William J. author. aut Link
X, 227 p.
Keywords: This book is a study of Anglo-French relations and military policy making in the First World War, which considers the strategic policies and operational planning of the British and French armies in the joint campaign fought on the western front. It examines the influence of incompatible British and French strategic objectives, the role of the allies' military and political leaders and the institutional development of the military alliance, on the alliance relationship and military policy making.